Swedish university student-athletes` dual career scenarios and competences - Linnér, L.; Stambulova, N. B.; Lindahl, K.; Wylleman, P. (International Journal of Sport and Exercise Psychology, 2025)
The paper presents the Swedish data on university student-athletes` dual career (DC) competences and coping, from the European project "Gold in Education and Elite Sport" (GEES). A cross-sectional quantitative design was implemented with the objectives to explore: (a) the student-athletes` perceived need to develop DC competences in order to successfully combine sport and study, (b) if the student-athletes experienced and how they coped with specific DC scenarios, and (c) the magnitude of the association between the student-athletes` possession of prioritised DC competences for each scenario and their scenario-specific coping. Seventy-one university student-athletes with a mean age of 25.21 completed the DC competency questionnaires developed within GEES. The student-athletes reported their perception of importance and possession of 38 DC competences (e.g. cope with stress, prioritising), as well as coping with seven DC scenarios (e.g. miss significant days of study), and selected the five most important competences (from the list of 38) to cope with each scenario. The results revealed that the student-athletes: (a) perceived a need to develop more than 70% of the DC competences to successfully combine sport and studies, (b) had experienced and coped average-to-good with the DC scenarios, and (c) possession of the top five prioritised competences was moderately-to-strongly related to their coping in three scenarios. The study extends understanding of Swedish university student-athletes` DC competences and has contributed to the development of Swedish National Guidelines for elite athletes` dual careers (2018).